PLACE MARKETING CHALLENGES AND THE CREATION OF CITY IDENTITY IN POLAND - Piechna, Anna; Renigier-Biłozor, Małgorzata (Acta Scientiarum Polonorum. Oeconomia, 2010)
The paper presents the scope of place marketing activities undertaken in Polish cities, referring to the example of the city of Olsztyn. It discusses the solutions and tasks related to the creation of city identity and new mental maps of cities and regions. The main goal of a place marketing project implemented in a given area is to develop a sense of community and belonging to a region, as well as social, shared responsibility which is the key factor determining the attractiveness of cities and regions. Following an analysis of the current state and the stage of realization of place marketing activities in the city of Olsztyn, a concept was proposed to use certain local products in order to establish and strengthen bonds with the place of residence and to build an internal identity. Another objective of the study was to stress that large parts of the city potential remain unused, and to identify the actions that should be taken to improve living conditions for the local residents and to attract more tourists.